The Reality Of The Islamisation Of Science - Hasan Bakti Nasution; Syahrul Holid; Suswanto (Fakultas Agama Islam Universitas Wiralodra, 2023)
Advances in science and technology bring negative thinking so that the global crisis is on the other hand. Science and technology indeed provide happiness but contribute to the emergence of global and multidimensional crises. This triggers the awareness of some Muslims to reconstruct science with a major project of Islamization of science. This idea invites pros and cons among academics. The idea of ​​Islamization of science is essentially the idea of ​​finding a new modern science apart from religion and monotheism. This idea has been popular since the beginning of its declaration and has now become a topic of discussion among Muslims. The research that the researcher did using qualitative research methods and including literature research was aimed at studying the Islamization of science.